Neuropsychoanalysis in practice : brain, self, and objects - Northoff, Georg (Oxford University Press, 2011)
Is the Ego nothing but our brain? Are our mental and psychological states nothing but neuronal states of our brain? Though Sigmund Freud rejected a neuroscientific foundation for psychoanalysis, recent knowledge in neuroscience has provided novel insights into the brain and its neuronal mechanisms. This has also shed light on how the brain itself contributes to the differentiation between neuronal and psychological states. In Neuropsychoanalysis in Practice, Georg Northoff discusses the various neuronal mechanisms that may enable the transformation of neuronal into psychological states, looki.